Effect of Subtalar Fusion and Calcaneal Osteotomy on Function, Pain, and Gait Mechanics for Calcaneal Malunion. (September 2019) - Farouk, Amr; Ibrahim, Amr; Abd-Ella, Mohamed Mokhtar; El Ghazali, Sherif
Background: Calcaneal malunion is a common complication of nonoperative management of calcaneal fracture, which leads to a disruption of the biomechanics of the lower extremity, pain, and permanent disability. Our aim was to evaluate pain, function, and gait after combined subtalar joint fusion, calcaneal osteotomy, and lateral wall exostectomy for patients with neglected calcaneal fractures with malunion. Methods: Eighteen patients with malunited calcaneal fractures, varus deformity, and subtalar arthritis were operated upon and then followed up for 18 months. All cases were assessed clinically using the American Orthopaedic Foot & Ankle Society (AOFAS) and visual analog scale (VAS); radiologically by measuring the talar inclination, talocalcaneal and talus-first metatarsal angles, and talocalcaneal height; and biomechanically by measuring the stride duration, step width, comfortable speed, and ground reaction forces in relation to the body weight. Results: A significant improvement in AOFAS (59.8 preoperatively to 80.2 after 18 months) and VAS (61.1 preoperatively to 29.4) was found. Also, our study revealed a significant improvement in the radiographic measurements including the valgus angle, the talocalcaneal angle, the talocalcaneal height, and the talar inclination angle. The gait analysis found that the maximum loading force in the push-off phase and comfortable speed yielded a significant improvement postoperatively. However, no significant differences between the preoperative data and the final follow-up in terms of the step width, stride duration, maximum peak force during loading phase, and minimum peak force during midstance phase were found. Conclusion: The combination of valgus calcaneal osteotomy, lateral wall exostectomy, and subtalar fusion resulted in pain reduction, improved function, and better gait. However, the limited bone stock for the graft used in the subtalar fusion made use of this technique in severely reduced height unadvisable. Level of Evidence: Level IV, case series.